A qualitative study on emergency health care worker (EHCW) prception towards COVID-ACLS simulation training in resuscitating suspected COVID-19 patients - Jebby Yii; Alias Mahmud; Azlan Helmy Abd Samat; Dazlin Masdiana Sabardin; Mohd Hisham Mohd Isa; Ismail Mohd Saiboon; Mohd Johar Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2021)
The emergence of COVID-19 pandemic has caused difficulty to emergency-HCW (EHCW) in resuscitating high-risk patients. We set out to explore EHCW’s perception after undergoing COVID-ACLS resuscitation training and address their anxiety of working in this pandemic. A qualitative case study using focused group discussion was conducted among EHCW who have undergone COVID-ACLS training. Five semi-structured questions exploring respondent’s confidence level, anxiety factors, areas of improvement for COVID-ACLS and if this COVID-ACLS training is sufficient. Inductive and deductive thematic analysis approach was done to analyse the result. 20 EHCW participated in this study. Out of 4 themes, 11 subthemes were identified based on the respondents. They were acquired new knowledge, self-precaution, method of delivery, concerns of self and family members, stigmatisation, insufficient protective methods, underappreciation, regular training sessions, other modalities for learning, course duration; and unsatisfactory reading material. New knowledge and self-precaution were noted to be an important aspect that boosts confidence among EHCW. The main factor that increased anxiety was safety issues and disease spreading to family members, colleagues, and society. In conclusion, COVID-ACLS training is able to boost EHCW confidence in resuscitating high-risk patients. Factors leading to anxiety among EHCW should also be addressed during this pandemic to ensure psychological welfare and mental health are not affected. Regular training and utilisation of other teaching modalities such as video are perceived as a helpful adjunct in boosting their confidence. The utilisation of new training approach should be explored in enhancing EHCW’s knowledge and confidence.